OP89 Using Economic Evidence To Set Priorities In Ghana: The Case Of Malaria. (2017) - Addo, Rebecca; Hall, Jane; Goodall, Stephen; Haas, Marion
Abstract : INTRODUCTION: Malaria remains the number one cause of morbidity and mortality in Ghana. Since 1961, several malaria control strategies have been adopted, some of which were discontinued due to funding. In spite of the numerous malaria control strategies in place, its prevalence continues to rise. Priority setting using economic evidence has been proven to ensure efficient use of resources in a cost-effective manner (1). This study, therefore, sought to examine economic evaluation studies conducted on malaria in Ghana and their influence on malaria control policies. METHODS: A systematic search was conducted in databases including Medline and Embase to identify relevant Malaria economic evaluation studies conducted in Ghana up to December 2016. Malaria control policies formulated in Ghana over the years were also reviewed. The economic studies were examined alongside the policies to establish their influence on them. RESULTS: A total of eight studies were identified, all of which were conducted in response to a global directive on malaria control and funded by international agencies. All studies were cost-effective; five evaluating preventive measures and the remaining evaluating treatment. The studies used different methodological approaches, rendering the comparison between alternatives impossible. Most malaria control initiatives are funded by international agencies, hence its abandonment when funding ceases. Although the majority of economic studies addressed some of these policies, none of them directly influenced their adoption. These policies were rather influenced by global malaria control initiatives. Also, malaria chemoprophylaxis; demonstrated as cost-effective by three studies, is not on the Ghana malaria control policy (2, 3). CONCLUSIONS: To ensure sustainability of malaria control strategies and subsequently reduce its prevalence, Ghana must invest financially into economic analysis for formulating and implementation of these policies. Also, the use of economic evidence by policy makers can be promoted, should researchers adopt a methodological guideline for its conduct that ensures comparability of results.